Spiritual well-being and associated factor among adult cancer patients in Hawassa University Comprehensive Specialized Hospital, Oncology Center, Hawassa, Ethiopia - Kebede, Fekadu Abera; Tafesse, Bontu Hailu; Moga, Fikre; Haile, Addisalem; Zerihun, Ebisa (Frontiers in Oncology, 2024)
Background: Spiritual well-being has been shown to boost resistance to mental health crises in cancer patients during the diagnosis and treatment process. But there is a paucity of study about spirituality in cancer patients; which may make it difficult for health care clinicians to assess spirituality and provide spiritual care.The aim of this study was to assess the level of spiritual well-being and associated factors among cancer patients in HUCSH oncology center by 2022.Institution based Cross-sectional study was done from May 30 to June 30/2022 among 267 cancer patients and respondents were selected with simple random sampling technique. Data was collected by using standardized interviewer administered questionnaires (FACIT sp12). Data was entered using Epi data version 4.6 and analysis by statistical package for social science version 25. Bivariate and multivariate logistic regression was conducted to determine the relationship between the independent and dependent variables. The strength of association was tested by using p value at 95% CI. Ethical clearance was obtained from Institutional Review Bored of Hawassa University College of medicine and health science. During data collection the purpose of the study was clearly explained to patients and consent was obtained.Result: 267 cancer patients were included in the study. There were 100% response rates.Majority of patients (80.5%) were in a poor spiritual wellbeing state. Mental distress (AOR=0.24 6; 95%CI 0.114, 0.531) and religious education (AOR=1.288; 95% CI 1.438, 9.142) were factors significantly associated with spiritual wellbeing among cancer patients.This study showed more than 2/3 rd of patients had poor spiritual wellbeing. Mental distress and religious education were factors associated with spiritual wellbeing. Attention should be given by nurses of the center for spiritual wellbeing assessment in clinical practices favoring holistic care in the center.